Functional diversity enhances grassland productivity, but species identity drives performance - Supriya Verma; Antje Herrmann; Friedhelm Taube; John Kormla Nyameasem; Daniel Ehrhard; Carsten S. Malisch; Christof Kluß; Arne Poyda (Agriculture, Ecosystems & Environment, 2026)

Temporal Changes to Migratory Fuel Load in Migratory Birds Across Europe - Jennifer Anne Border; Robert A. Robinson; James W. Pearce‐Higgins; Chris M. Hewson; Christine Howard; Philip A. Stephens; Stephen G. Willis; Jan A. C. von Rönn; Pierre‐Yves Henry; Romain Lorrilliere; Lorenzo Serra; Simona Imperio; et al. (Global Change Biology, 2025)
Climate change is a major threat to biodiversity, and migratory animals are particularly vulnerable, due partly to their reliance upon good resource availability across a network of sites at specific times. Migrants perform vital ecosystem functions, transferring significant resources across large spatial scales, but the impacts of climate change on the ability of individuals to complete these journeys are poorly studied. Collecting the large‐scale and long‐term data on the condition of individuals during migration to address this is challenging, but in migratory birds, we have a model system for which a large network of ringers (banders) collect individual data on body size and mass, enabling variation in body condition to be tracked. We used long‐term ringing data on 33 Afro–Palearctic migratory bird species at 286 sites across Europe to demonstrate a large‐scale decrease in migratory fuel loads during autumn over the last 40 years, but not in spring. Declines were strongest across southern Europe and linked to rising temperatures. The timing of autumn fuelling has also shifted, occurring earlier at northern sites and later at southern sites. These relationships varied depending on diet and breeding cycle length. Obligate insectivores were more constrained by temperature in the timing and magnitude of fuelling than frugivores. Species with short breeding cycles departed later at southern sites in warmer years, likely reflecting an extended breeding season. Altogether, these latitudinally varying findings suggest a trade‐off between maximising productivity or maximising adult survival as climate drives changing constraints on breeding season length and resource availability. Similar climate‐induced trade‐offs may be happening in other migratory taxa with the potential to influence population trends.

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

Rapid subsidence as a driver of phosphate deposition in the later Ordovician: Case study from the Alabama Appalachians - John T. Haynes; Rafael A. Villanueva; Richard M. Robinet; Stephen A. Leslie; Achim D. Herrmann (Sedimentary Geology, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Examining site intervention efficacy and uncertainties with conceptual Bayesian networks: preventing offsite migration of DNAPL and contaminated groundwater - John F. Carriger; Michael C. Brooks; Carolyn Acheson; Ronald Herrmann; Lee Rhea (Environmental Science and Pollution Research, 2024)

Bioeconomic analysis of harvesting within a predator–prey system: A case study in the Chesapeake Bay fisheries - Iordanka N. Panayotova; John Herrmann; Nathan Kolling (Ecological Modelling, 2023)

A framework for modelling soil structure dynamics induced by biological activity - Katharina Meurer; Jennie Barron; Claire Chenu; Elsa Coucheney; Matthew Fielding; Paul Hallett; Anke M. Herrmann; Thomas Keller; John Koestel; Mats Larsbo; Elisabet Lewan; Dani Or; et al. (Global Change Biology, 2020)
Soil degradation is a worsening global phenomenon driven by socio‐economic pressures, poor land management practices and climate change. A deterioration of soil structure at timescales ranging from seconds to centuries is implicated in most forms of soil degradation including the depletion of nutrients and organic matter, erosion and compaction. New soil–crop models that could account for soil structure dynamics at decadal to centennial timescales would provide insights into the relative importance of the various underlying physical (e.g. tillage, traffic compaction, swell/shrink and freeze/thaw) and biological (e.g. plant root growth, soil microbial and faunal activity) mechanisms, their impacts on soil hydrological processes and plant growth, as well as the relevant timescales of soil degradation and recovery. However, the development of such a model remains a challenge due to the enormous complexity of the interactions in the soil–plant system. In this paper, we focus on the impacts of biological processes on soil structure dynamics, especially the growth of plant roots and the activity of soil fauna and microorganisms. We first define what we mean by soil structure and then review current understanding of how these biological agents impact soil structure. We then develop a new framework for modelling soil structure dynamics, which is designed to be compatible with soil–crop models that operate at the soil profile scale and for long temporal scales (i.e. decades, centuries). We illustrate the modelling concept with a case study on the role of root growth and earthworm bioturbation in restoring the structure of a severely compacted soil.

Positive effects of the pollinators Osmia cornuta (Megachilidae) and Lucilia sericata (Calliphoridae) on strawberry quality - John David Herrmann; Henriette Beye; Christel de la Broise; Hollyn Hartlep; Tim Diekötter (Arthropod-Plant Interactions, 2019)

Connectivity increases trophic subsidies in fragmented landscapes - Christine L. Hawn; John D. Herrmann; Sean R. Griffin; Nick M. Haddad (Ecology Letters, 2018)
Landscape corridors mitigate the negative effects of habitat fragmentation by increasing dispersal. Corridors also increase biodiversity in connected habitat fragments, suggestive of metacommunity dynamics. What is unknown in this case is the mechanisms through which metacommunity dynamics act. Working in a large‐scale fragmentation experiment, we tested the effect of corridors on the movement of prey species and subsequent effects on predator nutrition (which we call trophic subsidies). We enriched plants of central patches with 15 N, then measured δ 15 N in green lynx spiders, the most abundant insect predator, in patches that were either connected to or isolated from the enriched patch. We found that corridors increased prey movement, as they increased spider δ 15 N by 40% in connected patches. Corridors also improved spider body condition, increasing nitrogen relative to carbon. We suggest a novel mechanism, trophic subsidies, through which corridors may increase the stability or size of populations in connected landscapes.

Diversity of root-associated arbuscular mycorrhizal fungal communities in a rubber tree plantation chronosequence in Northeast Thailand - Laetitia Herrmann; Didier Lesueur; Lambert Bräu; John Davison; Teele Jairus; Henri Robain; Agnès Robin; Martti Vasar; Wanpen Wiriyakitnateekul; Maarja Öpik (Mycorrhiza, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Connectivity from a different perspective: comparing seed dispersal kernels in connected vs. unfragmented landscapes - John D. Herrmann; Tomás A. Carlo; Lars A. Brudvig; Ellen I. Damschen; Nick M. Haddad; Douglas J. Levey; John L. Orrock; Joshua J. Tewksbury (Ecology, 2016)
Habitat fragmentation can create significant impediments to dispersal. A technique to increase dispersal between otherwise isolated fragments is the use of corridors. Although previous studies have compared dispersal between connected fragments to dispersal between unconnected fragments, it remains unknown how dispersal between fragments connected by a corridor compares to dispersal in unfragmented landscapes. To assess the extent to which corridors can restore dispersal in fragmented landscapes to levels observed in unfragmented landscapes, we employed a stable‐isotope marking technique to track seeds within four unfragmented landscapes and eight experimental landscapes with fragments connected by corridors. We studied two wind‐ and two bird‐dispersed plant species, because previous community‐based research showed that dispersal mode explains how connectivity effects vary among species. We constructed dispersal kernels for these species in unfragmented landscapes and connected fragments by marking seeds in the center of each landscape with 15 N and then recovering marked seeds in seed traps at distances up to 200 m. For the two wind‐dispersed plants, seed dispersal kernels were similar in unfragmented landscapes and connected fragments. In contrast, dispersal kernels of bird‐dispersed seeds were both affected by fragmentation and differed in the direction of the impact: Morella cerifera experienced more and Rhus copallina experienced less long‐distance dispersal in unfragmented than in connected landscapes. These results show that corridors can facilitate dispersal probabilities comparable to those observed in unfragmented landscapes. Although dispersal mode may provide useful broad predictions, we acknowledge that similar species may respond uniquely due to factors such as seasonality and disperser behavior. Our results further indicate that prior work has likely underestimated dispersal distances of wind‐dispersed plants and that factors altering long‐distance dispersal may have a greater impact on the spread of species than previously thought.

Minjingu phosphate rock applications increase the population of phosphate solubilising microorganisms with a positive impact on crop yields in a Kenyan Ferralsol - Keziah Wairimu Ndungu-Magiroi; Boaz Waswa; Andre Bationo; John Robert Okalebo; Caleb Othieno; Laetitia Herrmann; Didier Lesueur (Nutrient Cycling in Agroecosystems, 2015)

Commercial rhizobial inoculants significantly enhance growth and nitrogen fixation of a promiscuous soybean variety in Kenyan soils - Moses Thuita; Pieter Pypers; Laetitia Herrmann; Robert John Okalebo; Caleb Othieno; Esther Muema; Didier Lesueur (Biology and Fertility of Soils, 2012)

Differential effects of habitat isolation and landscape composition on wasps, bees, and their enemies - Christof Schüepp; John D. Herrmann; Felix Herzog; Martin H. Schmidt-Entling (Oecologia, 2011)

Cloning and functional analyses of the mouse tapasin promoter - Felix Herrmann; John Trowsdale; Christoph Huber; Barbara Seliger (Immunogenetics, 2003)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)